Serodiagnosis of chronic Chagas infection by using EIE-Recombinant-Chagas-Biomanguinhos kit - Gomes Yara M; Pereira Valéria RA; Nakazawa Mineo; Rosa Daniela S; Barros Maria das Neves DS; Ferreira Antonio GP; Silva Edimilson D; Ogatta Sueli F Yamada; Krieger Marco Aurélio; Goldenberg Samuel (Memorias do Instituto Oswaldo Cruz, 2001)
A kit based on an enzyme immunoassay, EIE-Recombinant-Chagas-Biomanguinhos, developed by the Oswaldo Cruz Foundation, was evaluated for the serodiagnosis of chronic Chagas disease. Evaluation was performed with 368 serum samples collected from individuals living in an endemic area for Chagas disease: 131 patients in the chronic phase with confirmed clinical, epidemiological, and serological diagnosis (indirect immunofluorescence, indirect hemagglutination or enzyme-linked immunosorbent assay) and 237 nonchagasic seronegative individuals were considered negative control. The EIE-Recombinant-Chagas-Biomanguinhos kit showed high sensitivity, 100% (CI 95%: 96.4-100%) and high specificity, 100% (CI 95%: 98-100%). The data obtained were in full agreement with clinical and conventional serology data. In addition, no cross-reaction was observed with sera from patients with cutaneous (n=14) and visceral (n=3) leishmaniasis. However, when these sera were tested by conventional serological assays for Chagas disease, cross-reactions were detected in 14.3% and 33.3% of the patients with cutaneous and visceral leishmaniasis, respectively. No cross-reactions were observed when sera from nonchagasic seronegative patients bearing other infectious disease (syphilis, n=8; HTLV, n=8; HCV, n=7 and HBV, n=12) were tested. In addition, sera of patients with inconclusive results for Chagas disease by conventional serology showed results in agreement with clinical evaluation, when tested by the kit. These results are relevant and indicate that the refered kit provides a safe immunodiagnosis of Chagas disease and could be used in blood bank screening.